Effect of Nitrogen Dosage (N) on Morphology of Soybean Strains (Glycine max (L.) Merr) Hold Bemisia tabaci - Endrik Nurrohman; Siti Zubaidah; Heru Kuswantoro (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2017)
Nutrients are needed by plants for the growth process and development. One crucial nutrient is nitrogen. Nitrogen triggers the formation and growth of vegetative parts of plants such as roots,stems and leaves. This study aimed to determine the effect of nitrogen dose against Glicine max. L strains UM.4-1, strains UM.7-2, strain UM.2-4, strains UM.7-6, strain UM.6-2, and two varieties namely Gumitir and Wilis resistant Bemisia tabaci. This experimental research was using a completely randomized block design with 4 treatment doses of nitrogen, 0 g, 25 g, 75 g and 100 g/polybag combined with 0,55g of potassium and phosphate 0,917g/polybag. The variables measured were length of petioles, the leaf ratio, leaf length, width and leaf area. Observations was carried out based on soybean lines, dosage, and a combination of both. Data were analyzed using 2-way ANOVA. The results showed that there were significant different in the lenght of petiole, leaf ratio, leaf length, width and leaf area on different strains of Glicine max. L. There was also the effect of different treatments (doses) on the length of petiole, leaf ratio, leaf width and leaf area but no significant effect on leaf length. Combination of treatments showing there were effect on the length of petiole, leaf ratio, leaf length and width and also on leaf area. Keywords: Nitrogen, morphologycal character, Glicine max.L.